Pengaruh Kemandirian Belajar Terhadap Prestasi Belajar Matematika Siswa Pada Materi Fungsi Komposisi Siswa Kelas X SMANS Pelita Ngabang - Paraya, Atiana; Ellssi, Wike (Papanda, 2025)
This study aims to analyze the effect of learning independence on students’ mathematics achievement in the topic of function composition among tenth-grade students of SMAS Pelita Ngabang. The research background indicates low test results, with 78.5% of students scoring below the minimum mastery criterion (KKM) on function composition. Employing a quantitative explanatory survey method, the independent variable was learning independence and the dependent variable was mathematics achievement. The population comprised all tenth-grade students of SMAS Pelita Ngabang in the 2024/2025 academic year, with a sample of 28 students selected through purposive sampling. Learning independence data were collected using a Likert-scale questionnaire based on five indicators (intrinsic motivation, discipline, initiative, self-confidence, and self-control), while achievement data were obtained through an essay test on function composition. Validity and reliability tests confirmed that all questionnaire items and test questions were valid and reliable.Data analysis included normality, linearity, and simple linear regression tests using SPSS 21. The results showed that the data were normally distributed and the variables had a linear relationship. The regression equation Y = 30.603 + 0.606X with a significance value of 0.001 < 0.05 indicates a positive and significant influence of learning independence on mathematics achievement. These findings highlight that enhancing students’ learning independence significantly contributes to academic performance, suggesting that teachers should implement strategies that foster student autonomy, particularly in mathematics topics requiring deep conceptual understanding.